Essays in linguistic ethnography ethics, aesthetics, encounters - Blackledge, Adrian 1959-; Creese, Angela 1959- (Multilingual Matters, 2023)
"This book argues for an approach to linguistic ethnography which departs from the perspective of the academic researcher, to amplify instead the voices of participants, researchers and collaborators. It reflects on ways of reporting research which add multiple perspectives and represent ambiguity more meaningfully than traditional academic prose"--
Includes bibliographical references and index
Keywords: Anthropological linguistics; Essays